Answer/Step-by-step explanation:
a. The mistake was "Going to Step 1".
The specific part of the problem that is wrong is[tex] (5^3) [/tex]
b. It is wrong because applying the negative exponent rule (i.e. [tex] \frac{1}{a^x} = a^{-x} [/tex], we should have:
[tex] (5^{-3}) [/tex] NOT [tex] (5^3) [/tex], because [tex] (\frac{1}{125}) = (5^{-3}) [/tex].
c. Here's how to work out the rest of the problem correctly.
[tex] 5^{x - 4} = (\frac{1}{125})^{2x + 1} [/tex]
1. [tex] 5^{x - 4} = (5^{-3})^{2x + 1} [/tex]
2. [tex] 5^{x - 4} = 5^{-6x - 3} [/tex] (distributive property)
3. [tex] x - 4 = -6x - 3 [/tex] (5 cancels 5)
4. [tex] 7x - 4 = - 3 [/tex] (addition property of equality)
5. [tex] 7x = 1 [/tex] (addition property of equality)
6. [tex] x = \frac{1}{7} [/tex] (division property of equality)